If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(5x + 8)(7x + -3) = 0 Reorder the terms: X(8 + 5x)(7x + -3) = 0 Reorder the terms: X(8 + 5x)(-3 + 7x) = 0 Multiply (8 + 5x) * (-3 + 7x) X(8(-3 + 7x) + 5x * (-3 + 7x)) = 0 X((-3 * 8 + 7x * 8) + 5x * (-3 + 7x)) = 0 X((-24 + 56x) + 5x * (-3 + 7x)) = 0 X(-24 + 56x + (-3 * 5x + 7x * 5x)) = 0 X(-24 + 56x + (-15x + 35x2)) = 0 Combine like terms: 56x + -15x = 41x X(-24 + 41x + 35x2) = 0 (-24 * X + 41x * X + 35x2 * X) = 0 (-24X + 41xX + 35x2X) = 0 Solving -24X + 41xX + 35x2X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'X'. X(-24 + 41x + 35x2) = 0 Factor a trinomial. X((-8 + -5x)(3 + -7x)) = 0Subproblem 1
Set the factor 'X' equal to zero and attempt to solve: Simplifying X = 0 Solving X = 0 Move all terms containing X to the left, all other terms to the right. Simplifying X = 0Subproblem 2
Set the factor '(-8 + -5x)' equal to zero and attempt to solve: Simplifying -8 + -5x = 0 Solving -8 + -5x = 0 Move all terms containing X to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -5x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -5x = 0 + 8 -5x = 0 + 8 Combine like terms: 0 + 8 = 8 -5x = 8 Add '5x' to each side of the equation. -5x + 5x = 8 + 5x Combine like terms: -5x + 5x = 0 0 = 8 + 5x Simplifying 0 = 8 + 5x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 3
Set the factor '(3 + -7x)' equal to zero and attempt to solve: Simplifying 3 + -7x = 0 Solving 3 + -7x = 0 Move all terms containing X to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -7x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -7x = 0 + -3 -7x = 0 + -3 Combine like terms: 0 + -3 = -3 -7x = -3 Add '7x' to each side of the equation. -7x + 7x = -3 + 7x Combine like terms: -7x + 7x = 0 0 = -3 + 7x Simplifying 0 = -3 + 7x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
X = {0}
| -36x=-720 | | -70x=-560 | | 126=x+92 | | 2+6x=2+4x | | 26x=-78 | | -32x=96 | | -3x=108 | | -48x=96 | | -26x=104 | | c^2=-2c+45 | | x^2+2ax+a^2-9=0 | | -x=397 | | 41-7x=160 | | c^2=2c+16 | | 4(3x-1)=6(x-1) | | 23+x=19+11 | | 4x+3.75=x-6 | | Y=7/17 | | 11.3y=4052 | | (2y-5x-4)-(x-6y+5)= | | 38-4=8 | | 8(x)+10=-9 | | x+78=97 | | 8(x)+10=9 | | x-(-53)=-123 | | (-3x-y+2)+(-2x+4y-9)= | | x-(-62)=-54 | | -3(y+5)-21=0 | | 10+-18+15z+z= | | 3x-7/2=x/3 | | x-(-33)=-75 | | 3(y+5)-21=-0 |